The Practical Potential of Bacilli and Their Enzymes for Industrial Production - Danilova, Iuliia; Sharipova, Margarita (Frontiers in Microbiology, 2020)
Bacillus spp. are an affordable source of enzymes due to their wide distribution, safety in work, ease of cultivation, and susceptibility to genetic transformations. Researchers are particularly interested in proteolytic enzymes, which constitute one of the most diverse groups of microbial proteins in terms of properties. Despite the long history of their research, this group of enzymes continue to show great potential for practical application in the biomedical industry, as well as in the agricultural industry. Thus, the unique properties of bacillary proteinases, such as stability in a wide range of temperatures and pH, high specificity, biodegradability of a wide range of substrates, and the high potential of sequenced Bacillus genomes are a powerful foundation for the development of new biotechnologies. The current review aims to discuss recent studies on various enzymes in particular, proteinases produced by bacteria of the genus Bacillus, along with their prospective practical applications. This article also presents an interpretive summary of the recent developments on the usage of probiotic Bacillus strains as potential feed additives.